Rewards in a Not-for-Profit Organisation - Kluvers , Ron; Tippet , John (Journal of Law and Governance, 2009)
This paper reports on a study undertaken in a Not-For-Profit (NFP) organisation providing services for people with disabilities. The organisation concerned is made up of two units and in response to a changing funding model, has introduced a performance bonus in one of the units. This situation raises the question as to how extrinsic rewards, as compared with intrinsic rewards, are perceived by staff of NFP organisations as a source of motivation. The effectiveness of an organisation is influenced by the motivation of its employees. Governance is concerned with enhancing the effectiveness of organisations. Because employee motivation impinges so critically upon effectiveness of the operations of the organisation, it is a governance issue. Data was gathered through a survey that had a number of statements about intrinsic and extrinsic rewards. The responses of the staff were indicated using a five-point Likert scale. The frequencies and percentages of those responses are reported in this study. The important findings of the study are that intrinsic rewards play a significant role in the motivation of staff in this NFP organisation. Extrinsic rewards were regarded in a more ambiguous way.